Parents’ and children’s beliefs about learning literacy and their relationships to literacy achievement in Grade 2 - Baranauskaitė, Emilė; Raižienė, Saulė; Šilinskas, Gintautas (Pedagogika, 2023)
Acquiring basic literacy skills is a crucial educational objective in elementary school. Studies have shown that as early as elementary school, children’s literacy skills are determined not by cognitive factors, but also by their learning motivation. According to Expectancy-Value theory (Eccles et al., 1983), students’ literacy motivation is a function of two motivational beliefs, that is, ability self-concept and subjective values in literacy, that are shaped by various social influences, such as parents’ expectations. The aim of the present study was to evaluate the relationships between students’ motivational beliefs in literacy, parents’ expectations and literacy achievement in second grade. 536 Grade 2 students (285 boys and 251 girls) as well as 536 of their parents participated in the study. Students' motivational beliefs about literacy were measured by Self-Concept of Ability scale (Viljaranta et al., 2016) and Task-Value Scale for Children (TVS-C; Aunola et al., 2006); parents' expectations were measured by Parental Beliefs scale (Aunola et al., 2002); students' first and second grade end-of-year marks in Lithuanian language were used as a measure of their literacy achievement. Results showed that students' ability beliefs, interest, parents’ expectations and Grade 1 achievement were positively related to each other. Literacy achievement in Grade 2 was predicted by Grade 1 achievement, parents’ expectations, beliefs about one’s ability, child’s gender and parents’ education level.